OPTIMIZATION OF COLD SPLICING PARAMETERS IN CONVEYOR BELT JOINTS ON SHEAR STRENGTH USING TAGUCHI METHOD - Alviari, Luana Putri; Choiron, Moch Agus; Tama, Ishardita Pambudi (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2022)
In the manufacturing industries, the main problem of material handling process using conveyor belt. Belt that continuously work will have damage or failure, so it repair by cold splicing. The purpose of this study is to see the effect of cold splicing parameters on the shear strength of conveyor belt joints based on variations in the number of belts, bias cut and adhesive thickness. Variations in the number of ply belts used are 2 ply, 3 ply and 4 ply, variations of cut bias 0.3xB, 0.6xB and 0.9xB and variations in the thickness of the adhesive which are 1 mm, 2 mm and 3 mm. This research was conducted experimentally using the Taguchi method based on shear test data using the Universal Testing Machine. Based on ANOVA value, the number of belt ply was high contribution by 86.22% with F-value = 155.3 and bias cut was lowest contribution by 0.23%.